The Effect of Using Reading Aloud on Pronunciation Ability - Rianti, Nur Peniy (Universitas Pahlawan Tuanku Tambusai, 2025)
This research investigated the effect of the reading aloud technique on the pronunciation ability of seventh-grade EFL students at SMPN 6 Cempaga. A quasi-experimental design was applied, involving 70 students who were divided into two groups: an experimental group taught through the reading aloud strategy and a control group taught using conventional methods. Data were collected through oral pre-tests and post-tests and were analyzed with non-parametric tests (Wilcoxon and Mann-Whitney) due to the non-normal data distribution. The results showed that the experimental group’s mean pronunciation score improved from 55.64 to 73.29, while the control group’s score increased from 54.00 to 67.79. Statistical analysis confirmed a significant difference (p 0.05) between the two groups. The findings demonstrated that the reading aloud technique effectively enhanced students’ English pronunciation. Therefore, it was recommended that teachers adopt reading aloud as a regular classroom practice to foster learners’ oral proficiency and confidence.